Complement and Kidney Disease - Zipfel, Peter F. (Progress in Inflammation Research, 2006)
It is evident that a defective or deregulated complement system results in kidney diseases. An important role of complement effector and regulatory proteins in pathological settings of the kidney has been demonstrated. A large panel of distinct human kidney diseases is caused by defective complement control. Genetic analyses have identified mutations in complement regulators that are associated with these diseases. Mutations have been identified in the fluid phase alternative pathway regulator Factor H and the membrane regulator Membrane Cofactor Protein MCP (CD46). The functional characterization of the mutant proteins allows to define the pathophysiological events on a molecular level. These new concepts and data on disease mechanisms allowed establishing new diagnostic and promising therapeutic approaches for several human kidney diseases. Molecular biology, clinics and therapy are discussed in this volume.